Development of Project-Based Learning Materials on Heat and Temperature to Train Student’s Scientific Skills - 'Aisyah Ummu Labiiq; Sukardiyono Sukardiyono (Berkala Ilmiah Pendidikan Fisika, 2021)
This research aims to produce project-based learning materials on temperature and heat, which are suitable for use in improving scientific skills and learning outcomes in cognitive aspects. The research and development method is carried out in seven steps: a preliminary study, planning, product draft development, limited trial, product draft revision, wider trial and initial product revision. Products are rated by seven validators. Limited trials were carried out on eight subjects, and more extensive trials were carried out on 32 subjects at Madrasah Aliyah Negeri Yogyakarta III using a one-group pretest-posttest design. The results of the study have shown that the product development Education Unit Level Curriculum version lesson plans, 2013 Curriculum version lesson plans, Project-Based Student Books and project appraisal sheets) are feasible. This use can improve scientific skills in learning but cannot significantly improve the test subjects' cognitive aspects' learning outcomes. Thus, Project-Based Student Books can be used as a learning medium by the teacher. However, it needs further improvement and research in order to improve scientific skills in learning.